Hydrogeological, hydrodynamic and anthropogenic factors affecting the spread of pharmaceuticals and pesticides in water resources from the Granada plain (Spain). - Llamas Dios, Marta Inés; Jiménez-Gavilán, Pablo; Luque Espinar, Juan Antonio; Benavente Herrera, José; Sanmiguel-Martí, M.; Rambla-Nebot, J.; Aranda-Mares, J.L.; Vadillo-Pérez, Iñaki (Elsevier, 2022)
The anthropogenic organic contaminants contemplated in the environmental legislation, as well as those of emerging concern, threaten the quality of water resources to a degree that remains largely unknown. Contam- inant exposure in the aquatic environment is a crucial element if a full understanding of the risk is pursued. There are still many uncertainties about the occurrence of organic pollutants and behavior in the hydro(geo)logical media in large scale areas. The case study of the unconfined aquifer of the Granada Plain (approximately 200 km2) is presented here. Two surface and groundwater monitoring campaigns were conducted (March 2017 and June 2018). In total, 41 out of 171 target organic pollutants were detected, at least once: 17 pharmaceuticals or drugs of abuse, 21 pesticides or their metabolites and three polyaromatic hydrocarbons. In addition, physico- chemical parameters were measured during the monitoring campaigns and hydrochemical parameters and sta- ble isotopes (δ2H, δ18O, δ13C) were analyzed. Statistical tests confirmed the significance of seasonal changes for some of these parameters (e.g., EC, Cl-, F-, δ18O, δ13C), revealing the influence from snowmelt water input on streams and the intensification of irrigation. In March 2017, the group of pesticides (largely represented by triazines) predominated, whereas the frequency of detection of pharmaceuticals increased substantially in June 2018. Results suggest four main factors affecting the spatial and seasonal variation of organic pollutants in the aquifer: the anthropogenic factor determining the period of contaminant release throughout the year (pesticide application period and growth of tourism) along with irrigation practices that include reclaimed wastewater; unsaturated zone thickness; hydraulic gradient and river-groundwater hydraulic connection.
Keywords: Gestión del agua - Efectos de los pesticidas - Vega de Granada (Granada, Comarca); Pharmaceuticals; Pesticides; Detrital aquifer; Seasonal variation; Unsaturated zone; Recharge process